Korelasi Konten Edukasi Postural di Media Sosial terhadap Pengetahuan Individu tentang Postural dan Exercise - Rinaldi Prima Saputra; Maulana Ahsan Fadhail; Zulfikar Zulfikar; Fatimah Wahab Aliyun; Rina Mayangsari (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Scoliosis is a complex three-dimensional deformity (lateral rotation) of the spine and waist. Scoliosis is defined as a condition in which there is a change in curvature of more than 100 on the outside of the spine. More severe structural scoliosis can be classified into idiopathic (the cause is known) and non- idiopathic (cause unknown). As a result of the problems that arise in these conditions, various communication media are becoming more sophisticated and diverse along with the development of science and technology. Researchers want to know the effect of social media content on training knowledge and compliance. The conclusion of this research was that the characteristics of the respondents were that there were 60 respondents (69.76%) with sufficient knowledge status. Meanwhile, 26 respondents (28.60%) did not have sufficient knowledge about posture correction and scoliosis. A total of 59 respondents (68.60%) had a sufficient level of compliance with exercise and 27 respondents (31.39%) had a poor level of compliance regarding good posture training for individuals with scoliosis.